Comparative Pathogenicity and Host Ranges of Magnaporthe oryzae and Related Species - Chung, Hyunjung; Goh, Jaeduk; Han, Seong-Sook; Roh, Jae-Hwan; Kim, Yangseon; Heu, Sunggi; Shim, Hyeong-Kwon; Jeong, Da Gyeong; Kang, In Jeong; Yang, Jung-Wook (The plant pathology journal, 2020)
Host shifting and host expansion of fungal plant pathogens increases the rate of emergence of new pathogens and the incidence of disease in various crops, which threaten global food security. Magnaporthe species cause serious disease in rice, namely rice blast disease, as well as in many alternative hosts, including wheat, barley, and millet. A severe outbreak of wheat blast due to Magnaporthe oryzae occurred recently in Bangladesh, after the fungus was introduced from South America, causing great loss of yield. This outbreak of wheat blast is of growing concern, because it might spread to adjacent wheat-producing areas. Therefore, it is important to understand the host range and population structure of M. oryzae and related species for determining the evolutionary relationships among Magnaporthe species and for managing blast disease in the field. Here, we collected isolates of M. oryzae and related species from various Poaceae species, including crops and weeds surrounding rice fields, in Korea and determined their phylogenetic relationships and host species specificity. Internal transcribed spacer-mediated phylogenetic analysis revealed that M. oryzae and related species are classified into four groups primarily including isolates from rice, crabgrass, millet and tall fescue. Based on pathogenicity assays, M. oryzae and related species can infect different Poaceae hosts and move among hosts, suggesting the potential for host shifting and host expansion in nature. These results provide important information on the diversification of M. oryzae and related species with a broad range of Poaceae as hosts in crop fields.Host shifting and host expansion of fungal plant pathogens increases the rate of emergence of new pathogens and the incidence of disease in various crops, which threaten global food security. Magnaporthe species cause serious disease in rice, namely rice blast disease, as well as in many alternative hosts, including wheat, barley, and millet. A severe outbreak of wheat blast due to Magnaporthe oryzae occurred recently in Bangladesh, after the fungus was introduced from South America, causing great loss of yield. This outbreak of wheat blast is of growing concern, because it might spread to adjacent wheat-producing areas. Therefore, it is important to understand the host range and population structure of M. oryzae and related species for determining the evolutionary relationships among Magnaporthe species and for managing blast disease in the field. Here, we collected isolates of M. oryzae and related species from various Poaceae species, including crops and weeds surrounding rice fields, in Korea and determined their phylogenetic relationships and host species specificity. Internal transcribed spacer-mediated phylogenetic analysis revealed that M. oryzae and related species are classified into four groups primarily including isolates from rice, crabgrass, millet and tall fescue. Based on pathogenicity assays, M. oryzae and related species can infect different Poaceae hosts and move among hosts, suggesting the potential for host shifting and host expansion in nature. These results provide important information on the diversification of M. oryzae and related species with a broad range of Poaceae as hosts in crop fields.